ANALISIS TINGKAT PEMAHAMAN PEMUDA TENTANG KATEKISASI DI JEMAAT GMIT SONHONIS OELBUBUK KLASIS KUPANG TENGAH - Marsi Bombongan Rantesalu; Adriana Pradahnata Bansole (Bethel Press, 2020)
Catechism is a forum for fostering and educating young people so that they can profess their faith before God and be witnessed by the Lord's congregation during the session. The catechism was designed for at least two years, one year to study the Bible and one year to outline the main points of the church's beliefs and the demands of Christian life in this world. The problem that occurs in the GMIT Sonhonis Oelbubuk is that the level of youth understanding of the teaching of catechism given by the instructor is very lacking. This study aims to find the level of youth understanding about catechism in the Church. The method used in this study is a survey technique with a quantitative approach. The population and sample are youth in the GMIT Sonhonis Oelbubuk. The results showed that the level of understanding of youth in the GMIT Sonhonis Oelbubuk about catechism was 79.53%, the results were included in the quite high category.